PENYELESAIAN NUMERIK SISTEM GETARAN TEREDAM DENGAN METODE RUNGE KUTTA ORDE EMPAT - , RIZQAN DESMAN; , Drs. Eko Sulistya, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A numerical solution of damped vibration has been done by using the fourthorder Runge-Kutta method in Microsoft Office Excel worksheet. The vibration system is modelled by a second-order differential equation that describes the damped vibration of mass ô connected to a rigid support by a linier spring with coefficient ôô¯¦, and a vibration damper with coefficient ôô¯. The second-order differential is tranformed to two first-order differential equation and then solved to find the three variables, namely the position ô, velocity ôâ², and acceleration ôâ²â² as a function of time ô. The soution is presented in the form of list of values and in graphs in Microsoft Office Excel worksheet.